Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's analyze the given equation [tex]\((x-4)(x+2) = 16\)[/tex] step-by-step to determine which of the provided statements is true.
1. Expanding and simplifying the equation:
Start with the given equation and expand the left-hand side.
[tex]\[ (x-4)(x+2) = 16 \][/tex]
When we expand [tex]\((x-4)(x+2)\)[/tex], we get:
[tex]\[ x^2 + 2x - 4x - 8 = x^2 - 2x - 8 \][/tex]
So the equation becomes:
[tex]\[ x^2 - 2x - 8 = 16 \][/tex]
2. Converting to standard form:
To convert this into a standard quadratic equation, we need to bring all terms to one side of the equation:
[tex]\[ x^2 - 2x - 8 - 16 = 0 \][/tex]
Simplify the left-hand side:
[tex]\[ x^2 - 2x - 24 = 0 \][/tex]
3. Examining each statement:
(a) The equation [tex]\(x-4=16\)[/tex] can be used to solve for a solution of the given equation.
No, this is not correct. The equation [tex]\(x - 4 = 16\)[/tex] does not directly relate to the given factored form of [tex]\((x-4)(x+2)=16\)[/tex].
(b) The standard form of the equation is [tex]\(x^2 - 2 x - 8 = 0\)[/tex].
No, the standard form derived from the equation [tex]\((x-4)(x+2) = 16\)[/tex] is [tex]\(x^2 - 2x - 24 = 0\)[/tex], not [tex]\(x^2 - 2x - 8 = 0\)[/tex].
(c) The factored form of the equation is [tex]\((x+4)(x-6)=0\)[/tex].
No, without solving the quadratic equation [tex]\(x^2 - 2x - 24 = 0\)[/tex], we cannot determine the factored form directly like [tex]\((x+4)(x-6)=0\)[/tex]. More importantly, we have not derived such a factorization.
(d) One solution of the equation is [tex]\(x = -6\)[/tex].
While we have not solved the equation [tex]\(x^2 - 2x - 24 = 0\)[/tex] to find the roots, the standard form transformation itself doesn't give us the roots directly. We need to solve the quadratic equation first to verify.
Given our detailed steps and analysis:
- By expanding the left side of the given equation, the correct standard form is indeed [tex]\(x^2 - 2 x - 24 = 0\)[/tex].
Thus, none of the provided statements are true based on the derived standard form and our mathematical derivations from the given equation [tex]\((x-4)(x+2) = 16\)[/tex].
1. Expanding and simplifying the equation:
Start with the given equation and expand the left-hand side.
[tex]\[ (x-4)(x+2) = 16 \][/tex]
When we expand [tex]\((x-4)(x+2)\)[/tex], we get:
[tex]\[ x^2 + 2x - 4x - 8 = x^2 - 2x - 8 \][/tex]
So the equation becomes:
[tex]\[ x^2 - 2x - 8 = 16 \][/tex]
2. Converting to standard form:
To convert this into a standard quadratic equation, we need to bring all terms to one side of the equation:
[tex]\[ x^2 - 2x - 8 - 16 = 0 \][/tex]
Simplify the left-hand side:
[tex]\[ x^2 - 2x - 24 = 0 \][/tex]
3. Examining each statement:
(a) The equation [tex]\(x-4=16\)[/tex] can be used to solve for a solution of the given equation.
No, this is not correct. The equation [tex]\(x - 4 = 16\)[/tex] does not directly relate to the given factored form of [tex]\((x-4)(x+2)=16\)[/tex].
(b) The standard form of the equation is [tex]\(x^2 - 2 x - 8 = 0\)[/tex].
No, the standard form derived from the equation [tex]\((x-4)(x+2) = 16\)[/tex] is [tex]\(x^2 - 2x - 24 = 0\)[/tex], not [tex]\(x^2 - 2x - 8 = 0\)[/tex].
(c) The factored form of the equation is [tex]\((x+4)(x-6)=0\)[/tex].
No, without solving the quadratic equation [tex]\(x^2 - 2x - 24 = 0\)[/tex], we cannot determine the factored form directly like [tex]\((x+4)(x-6)=0\)[/tex]. More importantly, we have not derived such a factorization.
(d) One solution of the equation is [tex]\(x = -6\)[/tex].
While we have not solved the equation [tex]\(x^2 - 2x - 24 = 0\)[/tex] to find the roots, the standard form transformation itself doesn't give us the roots directly. We need to solve the quadratic equation first to verify.
Given our detailed steps and analysis:
- By expanding the left side of the given equation, the correct standard form is indeed [tex]\(x^2 - 2 x - 24 = 0\)[/tex].
Thus, none of the provided statements are true based on the derived standard form and our mathematical derivations from the given equation [tex]\((x-4)(x+2) = 16\)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.